Penerapan Media Crossword Puzzle untuk Meningkatkan Minat Belajar Peserta Didik pada Mata Pelajaran SKI - Hapsah Fauziah; Delisna Isnaulianti (STAI Al-Musaddadiyah Garut, 2026)
This study discusses increasing learning interest through the implementation of crossword puzzles at MTs. An-Nashr. Strong and positive learning interest in the learning process is characterized by curiosity, interest, and enjoyment in learning. This study aims to determine the effectiveness of implementing crossword puzzles in increasing student learning interest. The research method used is the Classroom Action Research (CAR) method. Research instruments are tools for collecting data, which also reflect the implementation techniques. Without the right instruments, research results will not be optimal. Therefore, the research instruments used in Classroom Action Research (CAR) include questionnaires and observation sheets. The Classroom Action Research that the researcher will conduct will use the Kemmis & McTaggart model. The results of the study indicate that the application of crossword puzzle media can significantly increase student learning interest. Crossword media can be an alternative to increase student learning interest and can be used as an effective learning strategy. The total increase that occurred from the pre-cycle to the second cycle was 52.34% to 89.1%. Thus, it can be concluded that crossword puzzle media can increase student learning interest. Keywords: Crossword Puzzle Media, Learning Interest, SKI